PENGARUH LATIHAN WALL-PASS TERHADAP KETERAMPILAN PASSING PADA EKSTARKURIKULER FUTSAL DI MAN 10 JAKARTA - Fazari, Nadhil; Rhama Nurwansyah Sumarsono; Ardawi Sumanro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of implementing wall-pass training on improving the passing skills of futsal extracurricular participants at MAN 10 Jakarta. This research method uses a quantitative method with a pre-experimental approach and uses a One Group Pre-test Post-test Design research design to determine the differences before and after being given certain treatments. The sample used in this study used a total sampling technique and the samples taken were 20 people. Using basic movement assessment instruments as instruments in the study. The results of the normality test data processing produced a pretest significance of 0.085 while the posttest was 0.069. From these data it can be interpreted that the normality test is normally distributed, because the significance is> 0.05. Then a homogeneity test was carried out which produced a significance value of 0.451. From these data it can be interpreted that the homogeneity test is homogeneous. Then a Paired Sample T-test was carried out to determine the resulting effect with a value of 0.000. So, it can be said to have an effect because <0.05. This study found that basic passing technique skills (after using the application of the wallpass training method increased from the initial test). This shows that the implementation of wall pass training can improve basic passing technique skills in futsal extracurricular participants at one of the Islamic high schools in Joglo, West Jakarta.